Analysis of the Role of the Union Generale Tunisienne du Travail (UTT) in the Democratization Transition in Tunisia - Rahma, Alya Fitriany; Mas'udi, Syasya Yuania Fadila (WIMAYA, 2023)
This research aims to analyze the position of the Union Generale Tunisienne du Travail (UGTT) which is a combination of trade unions and labor unions in Tunisia in influencing the country's political stability during the time of the Arab revolution or what is known as the Arab Spring. This research analysis uses the concept of civil society to see the role of trade unions in Tunisia in building their political power. This research uses a qualitative method with library research (library research) which is classified and grouped based on several collections of written materials from various sources of books, scientific articles, and the internet. The results of the study show that the UGTT has two roles in achieving the goals of Tunisia's democratization, firstly as a power intermediary, where the UGTT functions in uniting the population and the government by chairing dialogue and guiding decision making during an unstable period. Second, the UGTT also plays a role as a key mediator in the democratization transition process by participating in the policy-making process, namely working with members of parliament in drafting a new constitution.